1177 Impact of 4% Chlorhexidine Cord Cleansing of Umbilical Cord on Bacterial Growth of Newborns in Pemba, Tanzania. (October 2012) - Sazawal, S; Dhingra, U; Madhesiya, S; Dutta, A; Ali, SM; Ame, S; Deb, S; Black, R
Abstract : Introduction: Studies in Nepal, Pakistan, and Bangladesh have shown using 4% CHX solution for umbilical cord cleansing reduces neonatal mortality and omphalitis. Data evaluating the effect of 4% Chlorhexidine umbilical cord cleansing from the Sub-Saharan region is lacking. Considering this need we are undertaking a double blind, controlled study in Eastern Africa. Before starting the trial, in this pilot we tested the impact of 4% Chlorhexidine and control solution specially prepared for the trial on colonization and colony count. Methods: Total 512 newborns in both the hospital and community were enrolled in the study. Newborns were randomly assigned the Chlorhexidine, placebo or dry cord care group. Umbilical swabs were collected at baseline (before the application of intervention), 2 hour and 48 hour after application of the assigned intervention. Presence of growth, identification to gram positive/negative groups and semi-quantitative colony count was estimated for all samples. Results: The positivity was high baseline swabs 30% (154 of 512 samples). In 2 hour post intervention group Chlorhexidine significantly reduced the growth of pathogens compared to placebo (OR 0.15, p< 0.01) and dry cord [OR 0.07, p=0.00]. In 48-hour swabs reduction in growth and density of organisms was observed in Chlorhexidine group (OR 0.11, p<0.01). There was no difference between the control solution and dry cord group (OR 0.97, p=0.92). Conclusions: Chlorhexidine preparation was effective in reducing the growth and density of pathogens over the umbilical cord. The control preparation did not increase colonization but was similar to dry cord care group.